t(4;11) (q21;q23) in acute myeloid leukemia-M0 following treatment [EW92 Protocol] for Ewing's sarcoma - Salles,Terezinha J. Marques (2004)
We report on a 7-year-old girl with Ewing's Sarcoma (ES) who developed a poorly differentiated acute myeloid leukemia (AML-M0) 20 months after beginning the EW92 protocol for the treatment of the primary tumor. She received a total dose of 1500 mg of etoposide, a tumor cumulative radiation dose of 35Gy and granulocyte colony-stimulating factor (G-CSF) was as predicted in the protocol regimen. At onset of secondary malignancy her laboratorial analysis revealed immature blast cells characterized by CD34+/CD33-/a-MPO+ and a t(4;11)(q21;q23) abnormality. This serious complication of ES treatment, which associates etoposide, irradiation and G-CSF schedule, should be weighed against its therapeutic benefits.